Efficacy and safety of AXS‐05, a novel oral NMDA receptor antagonist with multimodal activity in agitation associated with Alzheimer's disease: Results from ADVANCE‐1 — A phase 2/3, double‐blind, active and placebo‐controlled trial: Neuropsychiatry and behavioral neurology/Assessment/Measurement of neuropsychiatric/Behavioral and psychological symptoms. (7th December 2020) - O'Gorman, Cedric; Jones, Amanda; Cummings, Jeffrey L.; Tabuteau, Herriot
Abstract: Background: AXS‐05 (dextromethorphan/bupropion modulated delivery tablet) is a novel, oral, non‐competitive NMDA receptor antagonist with activity on other neurotransmitter systems (sigma‐1, serotonin, norepinephrine, and dopamine) which have been implicated in the cognitive and behavioral abnormalities of Alzheimer's disease (AD). Up to 70% of patients with AD experience agitation. AD agitation is associated with accelerated cognitive decline, early institutionalization, increased mortality, and increased caregiver burden. There are no approved pharmacological treatments for AD agitation. Method: The ADVANCE‐1 trial was a Phase 2/3, randomized, double‐blind, controlled, 5‐week study of AXS‐05 in AD agitation. Patients were randomized to treatment with AXS‐05, placebo, or bupropion. The primary endpoint was the change from baseline in the Cohen Mansfield Agitation Inventory (CMAI). The modified Alzheimer's Disease Cooperative Study‐Clinical Global Impression of Change for Agitation (mADCS‐CGIC) was a key secondary endpoint. Result: 366 AD patients with clinically significant agitation were randomized to AXS‐05 (n=159), bupropion (n=49), and placebo (n=158). On the primary endpoint, AXS‐05 significantly relieved agitation, demonstrating a change from baseline in the CMAI total score of 15.4 compared to 11.5 for placebo (p=0.010) and 10.0 for bupropion (p<0.001). These results represent a mean percentage reduction from baseline of 48% for AXS‐05 versus 38% for placebo. AXS‐05 was numerically superior to placebo starting at Week 2, achieving statistical significance at Week 3 (p=0.007) only one week after full dosing with AXS‐05. AXS‐05 demonstrated clinical response (≥30% improvement on the CMAI) in 73% of patients compared to 57% for placebo (p=0.005). AXS‐05 demonstrated statistically significant improvements in agitation as compared to placebo on the mADCS‐CGIC (p=0.036). The most commonly reported AEs with AXS‐05 were somnolence (8.2% AXS‐05, 4.1% bupropion, 3.2% placebo), dizziness (6.3%, 10.2%, 3.2%, respectively), and diarrhea (4.4%, 6.1%, 4.4%, respectively). There was no evidence of cognitive decline or sedation with AXS‐05. Conclusion: In the ADVANCE‐1 Phase 2/3 trial, AXS‐05 rapidly, substantially, and significantly improved agitation in patients with AD as compared to placebo. AXS‐05 was well tolerated and not associated with cognitive decline or sedation.